Multitoxin evaluation in fermented beverages and cork stoppers by liquid chromatography–tandem mass spectrometry. (11th September 2012) - Scussel, Vildes M.; Scholten, Jos M.; Rensen, Peter M.; Spanjer, Martien C.; Giordano, Barbara N. E.; Savi, Geovana D.
Summary A total of twenty‐eight mycotoxins were surveyed in wine (red, white and rose), cider (white and rose) and their cork stoppers from eight countries. Toxins of different fungi genera were detected as follows: Alternaria (ATs: alternariol – AOH; alternariol methyl – AME) and Penicillium/Aspergillus (ochratoxin A – OTA; penicillic acid – PAC). Toxins and levels varied with the sample types and country of origin. Wine presented contamination of OTA, AOH and AME. OTA was detected in forty‐one wine samples with levels ranging from 0.01 to 0.86 μg L−1, below EU legislation. AOH and AME were detected in thirty‐three and eight of wines samples, respectively, at levels from 0.2 to 13.3 μg L−1, while no contamination was detected in ciders up to the method LOQs. Regarding the cork stoppers toxins detected, they were AOH, AME and PAC. Corks of red wine from different countries had levels of OAH and AME ranging from 5.0 to 101.0 and 2.5 to 5 μg g−1, respectively. It is necessary to pay more attention on the corks processing and cork type used in the bottles as, different from the ordinary ones, the ground bark and compressed type did not have toxins detected.